Cultivating Cipasung Tourism Village: The Tourism Awareness Group Program (POKDARWIS) in Majalengka Regency - Aldi Dwi Cahyo; Frisky Diaslestarie; Belardo Prasetya Mega Jaya (Faculty of Law, Universitas Sultan Ageng Tirtayasa, 2022)
Tourism development requires support from various stakeholders. The Ministry of Tourism and Creative Economy made a regulation that required tourist villages to create tourism awareness groups or Pokdarwis. Through the community service program in Cipasung Village, Lemah Sugih District, Majalengka Regency, socialization and discussions about Pokdarwis were carried out to create tourism development in Cipasung Village which could be managed by the Cipasung Village community, especially youth. The group that will become partners is the youth of Cipasung Village Youth Organization and Cipasung Village government apparatus which includes RT, RW, and Village Head. The lecture method was used to deliver guidelines for planning and implementing Pokdarwis as well as a discussion forum which was divided into several groups with different themes. Socialization and discussion about the potential of the village can increase awareness, explore bright ideas, and can increase people's motivation and optimism to develop tourism potential in Cipasung Village.